Changes in dip of subducted slabs at depth: petrological and geochronological evidence from HP-UHP rocks (Tianshan, NW-China). - Klemd, Reiner; John, Timm; Scherer, E. E.; Rondenay, Stephane; Gao, J. (Earth and Planetary Science Letters, 2011)
High-resolution seismic imaging has previously revealed sudden changes in the dip of subducted oceanic plates. This 'kinking' feature is crucial because in many subduction zones it is thought to coincide with the disappearance of the low-velocity layers associated with subducted oceanic crust. In this study, we present petrological evidence for this phenomenon derived from oceanic blueschist- and eclogite-facies rocks from the Chinese Tianshan. The investigated samples span a large range of peak metamorphic conditions, with temperatures between 330 and 580°C at 1.5 to 2.3GPa. Such variable peak metamorphic conditions, together with the intimate interlayering of high- and ultrahigh-pressure rocks, have also been reported from other Tianshan localities. These observations suggest that the rocks were derived from varying depths within the subduction zone and then juxtaposed during exhumation in the subduction channel. Multi-point Lu-Hf isochrons from four high-pressure rocks yield consistent garnet-growth ages of 313±12, 315.8±2.9, 313.9±4.8, and 315.2±1.6Ma. These, in conjunction with the 311Ma cluster of published 40Ar-39Ar and Rb-Sr white mica ages from the same vicinities imply fast exhumation rates. The Lu-Hf ages confirm that the eclogite-facies metamorphism of the Tianshan high-pressure rocks occurred during a single subduction event in the Late Carboniferous. However, the previously reported peak metamorphic P-T estimates from UHP metasediments and eclogites all lie on a lower geothermal gradient - and thus on a colder P-T path at the slab-wedge interface - than the HP eclogites and meta-volcaniclastic rocks from this study. This suggests that the slab-subduction angle steepened sharply at a depth greater than approximately 90km, i.e., between the depths at which the HP and UHP rocks equilibrated. In addition to the negative buoyancy of mafic UHP rocks in subduction zones, the kinking may act as a geometric hindrance to the exhumation of such rocks, thereby explaining their rarity. © 2011 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.c3geoc.change
Keywords: (U)HP rocks; Lu-Hf geochronology; Oceanic crust; Slab dip steepening; Subduction; Tianshan